Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
A. 5+x-12=2x-7
-7+x+2x-7
x=2x
x-2x=0
-x=0-> x=0
B.
when X=-0.5
5+(-0.5)-12=2 (-0.5)-7
-7.5=-8 (answer does not work)
when X=0
5+0-12=2(0)-7
-7=-7 (answer works)
when x=1
5+1-12=2(1)-7
18=-5 (answer does not work)
Step-by-step explanation:
Answer:
[tex]x=0[/tex]
Step-by-step explanation:
A) From this case you would need to narrow down the whole equation...
Like this: [tex]5+x-12=2x-7[/tex] → [tex]x-7=2x-7[/tex] → [tex]x=0[/tex]
B) To prove that one of these numbers solve the equation, we would have to check it ourselves.
Like this: [tex]5+(-0.5)-12=2(-0.5)-7[/tex] → [tex]-7.5=-8[/tex] (SO THIS WON'T WORK)
[tex]5+0-12=2*0-7[/tex] → [tex]0=0[/tex] (THIS WORKS!)
[tex]5+1-12=2(1)-7[/tex] → [tex]-6=-5[/tex] (NOR DOES THIS WORK)
Therefore: [tex]x=0[/tex] will work to solve the equation correctly
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.